Increasing Students' Learning Interest and Scientific Attitude Through Flipped Classroom Blogs on Work and Energy Learning in Grad X Senior High School - Azizah, Nurul; Nasir, Muhammad; Rahmad, M. (Journal of Indonesian Science Teachers, 2023)
The purpose of this research is to describe an increase in students' interest in learning and scientific attitudes through the application of the flipped classroom blog on work and energy material in class X SMAN 5 Pekanbaru. This type of research used quasi-experimental, where the experimental class implemented the flipped classroom blog, while the control class used conventional learning. This research uses an instrument in the form of a questionnaire of interest in learning and students' scientific attitudes. Data were analyzed descriptively and inferentially to see an increase in students' learning interests and scientific attitudes. The results of the research obtained an average score of learning interest in classes using the flipped classroom blog in learning of 3.02 in the moderate category with a gain of 0.4 while for scientific attitude after implementing the flipped classroom blog, it was 3.04 in the medium category with a gain of 0.3. Thus, both the interest in learning and the scientific attitude of the experimental class students got better results than the control class. Based on the hypothesis testing carried out, there was a significant increase in students' interest and scientific attitude in learning the material of work and energy. Therefore, the use of the flipped classroom blog can increase students' interest and scientific attitude in learning physics on work and energy material at SMAN 5 Pekanbaru.